Helpless Dependents or Active Independents: A Cluster Analysis of Elders in China - Cai, Yi; Yang, Yali; Guo, Ping (Social indicators research, 2014)
The current study aimed to gain a better understanding of Chinese seniors' demographic information as well as their attitudes toward old-age support as an indicator for their subjective well-being related to their retirement preparation. Particularly, the variation of demographic and attitudinal characteristics within the population was examined. The data was based on a sample of the Chinese senior population, aged 60 and over in 2006 from 20 provinces and metropolitan areas in China. A two-step cluster analysis was used in the current study and the auto-clustering algorithm indicated a two-cluster solution. Both demographic information and attitudinal responses were used for the clusters. The results showed that Chinese seniors' attitudinal and behavioral traits were relevant to the classification with regard to their retirement preparedness. The current study demonstrated that Chinese seniors were a heterogeneous group that could be divided into two basic, distinct segments, namely, helpless dependents and active independents. Each different group of seniors may raise different key issues in meeting their needs for retirement management.